Teach for Qatar: Teachers' Challenges and Resources in Qatar's Government Schools. (May 2022) - Romanowski, Michael H.; Qadhi, Saba Mansoor
Launched in 2014, Teach for Qatar (TFQ) is a local non-governmental organization under Teach For All (TFALL) that recruits and prepares graduates and professionals as teaching fellows in the Qatari government schools. This qualitative exploratory study used semi-structured interviews to identify TFQ Fellows' challenges they faced and the resources available during their teaching in Qatar's Government Schools. Findings indicate that these TFQ Fellows experienced similar challenges that TFALL participants face worldwide and regional, including unreal expectations, unexpected workloads, and unmotivated and unprepared students. It was reported that TFQ provides a comprehensive and valuable resource and support system that enabled these individuals to complete their 2-year commitment. The discussion offers additional insights into the TFQ program and how these findings might benefit teacher education programs and programs like TFQ.